2017
DOI: 10.1155/2017/3452513
|View full text |Cite
|
Sign up to set email alerts
|

The Burden and Trend of Blood-Borne Pathogens among Asymptomatic Adult Population in Akwatia: A Retrospective Study at the St. Dominic Hospital, Ghana

Abstract: Background This study was aimed at evaluating the seroprevalence and trend of blood-borne pathogens (HIV, HCV, HBV, and Syphilis) among asymptomatic adults at Akwatia during a four-year period (2013–2016). Materials and Methods The study was a retrospective analysis of secondary data of blood donors who visited the hospital from January 2013 to December 2016. Archival data from 11,436 prospective donors was extracted. Data included age, sex, and place of residence as well as results of infectious markers (HIV,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 25 publications
3
14
2
Order By: Relevance
“… 20 In another way, the sero-prevalence finding in the current study is slight higher as compared to previous reports from different parts of Ethiopia, such as Debre Tabor (4.6%), 21 and North Shoa, central Ethiopia (2.4%). 8 Likewise, the rate of TTIs in the current study is somehow higher than different research reports from other countries, like Eritrea (3.6%), 22 Ghana (4.06%), 23 India (4.36%), 24 and Pakistan (5.8%). 1 The possible reasons for the discrepancy in the total sero-prevalence of TTIs between various studies could be variation in the total sample size, in the nature of the study population, research method used, time period, the test kits on the market, storage, and validation of the test kits.…”
Section: Discussioncontrasting
confidence: 67%
“… 20 In another way, the sero-prevalence finding in the current study is slight higher as compared to previous reports from different parts of Ethiopia, such as Debre Tabor (4.6%), 21 and North Shoa, central Ethiopia (2.4%). 8 Likewise, the rate of TTIs in the current study is somehow higher than different research reports from other countries, like Eritrea (3.6%), 22 Ghana (4.06%), 23 India (4.36%), 24 and Pakistan (5.8%). 1 The possible reasons for the discrepancy in the total sero-prevalence of TTIs between various studies could be variation in the total sample size, in the nature of the study population, research method used, time period, the test kits on the market, storage, and validation of the test kits.…”
Section: Discussioncontrasting
confidence: 67%
“…The overall pooled prevalence of infectious markers in our study was 4.36%. Earlier studies from India 17 (4.36%), Ghana 18 (4.06%), Pakistan 19 (4.0%), and Eritrea 20 (3.6%) have reported a similar trend. However, the percentage was on the lower side when compared with Nigeria 21 (28.8%), Bangladesh 16 (7.8%), Ethiopia 22 (11.5%), and Tanzania 11 (10.1%).…”
Section: Discussionsupporting
confidence: 55%
“…A total of three studies [32][33][34] reported HBV prevalence among blood donors with a total sample size of 16 192 participants. The hepatitis B prevalence ranged from 6.94% to 7.50% with a pooled prevalence of 7.17% (CI: 6.78-7.57) (S3 Appendix).…”
Section: Prevalence Of Hepatitis B Among Blood Donorsmentioning
confidence: 99%